Pulsational instability of high-luminosity H-rich pre-white dwarf star - Calcaferro, Leila Magdalena (2017)
We present a pulsational stability analysis on high-luminosity H-rich (DA) white dwarf models evolved from low-metallicity progenitors. We found that the ϵ mechanism due to H-shell burning is able to excite low-order g modes.